Entrepreneurial motivation of culinary students through implementation of online heutagogy project-based learning for productive courses - Badraningsih Lastariwati; Titin Hera Widi Handayani; Tri Murhanjati Sholihah; Abdul Rasid Bin Abdul Razzaq (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The objectives of this study were to 1) implement online heutagogy Project Based Learning (PjBL) syntax in business-based practice courses, and 2) determine students' entrepreneurial motivation in the implementation of online heutagogy PJbL in business-based practice courses. This study was quantitative descriptive research that analyzed the actual condition of heutagogy PjBL implementation and collected online data from an entrepreneurial motivation questionnaire. The students from the Culinary Arts Education Study Program who took part in business-based practical/productive learning served as the research subjects. The data were descriptive quantitative with categories established in the form of a Likert scale following the regulations. The results showed that: 1) the implementation of online heutagogy PjBL was following the six steps of PjBL syntax, namely identifying problems or projects, designing project plans, preparing project schedules, project implementation, and monitoring, testing results, evaluating and reflecting 2) entrepreneurial motivation of culinary studentsthrough the implementation of online heutagogy PJbL in business-based practice courses obtained excellent categories on the sub-indicators of need for achievement with a percentage of 94.3%, locus of control with a percentage of 89.5%, vision, desire for independence with a percentage of 93.5%, passion with a percentage of 92.8%, drive with a percentage of 86.8%, goalsetting with a percentage of 89.1%, self-efficacy with a percentage of 89.3 and sub-indicator of risk-taking with a percentage of 82.1% in the good category. The objectives of this study were to 1) implement online heutagogy Project Based Learning (PjBL) syntax in business-based practice courses, and 2) determine students' entrepreneurial motivation in the implementation of online heutagogy PJbL in business-based practice courses. This study was quantitative descriptive research that analyzed the actual condition of heutagogy PjBL implementation and collected online data from an entrepreneurial motivation questionnaire. The students from the Culinary Arts Education Study Program who took part in business-based practical/productive learning served as the research subjects. The data were descriptive quantitative with categories established in the form of a Likert scale following the regulations. The results showed that: 1) the implementation of online heutagogy PjBL was following the six steps of PjBL syntax, namely identifying problems or projects, designing project plans, preparing project schedules, project implementation, and monitoring, testing results, evaluating and reflecting 2) entrepreneurial motivation of culinary studentsthrough the implementation of online heutagogy PJbL in business-based practice courses obtained excellent categories on the sub-indicators of need for achievement with a percentage of 94.3%, locus of control with a percentage of 89.5%, vision, desire for independence with a percentage of 93.5%, passion with a percentage of 92.8%, drive with a percentage of 86.8%, goalsetting with a percentage of 89.1%, self-efficacy with a percentage of 89.3 and sub-indicator of risk-taking with a percentage of 82.1% in the good category.